Civilization, modernity, and critique: engaging Jóhann P. Árnason's macro-social theory - Ľubomír, Dunaj 19XX-; Smith, Jeremy; Mertel, Kurt Cihan Murat (Routledge studies in social and political thought, 2023)
"Civilization, Modernity, and Critique provides the first comprehensive, cutting edge engagement with the work of one of the most foundational figures in civilizational analysis: Johann P. Arnason. In order to do justice to Arnason's seminal and wide-ranging contributions to sociology, social theory and history, it brings together distinguished scholars from a variety of disciplinary backgrounds and geographical contexts. Through a critical, interdisciplinary dialogue, it offers an enrichment and expansion of the methodological, theoretical, and applicative scope of civilizational analysis, by addressing some of the most complex and pressing problems of contemporary global society. A unique and timely contribution to the ongoing task of advancing the project of a critical theory of society, this volume will appeal to scholars of sociology and social theory with interests in historical sociology, critical theory and civilizational analysis"--